2021
DOI: 10.3390/cancers13061422
|View full text |Cite
|
Sign up to set email alerts
|

Role of bFGF in Acquired Resistance upon Anti-VEGF Therapy in Cancer

Abstract: Anti-angiogenic approaches targeting the vascular endothelial growth factor (VEGF) signaling pathway have been a significant research focus during the past decades and are well established in clinical practice. Despite the expectations, their benefit is ephemeral in several diseases, including specific cancers. One of the most prominent side effects of the current, VEGF-based, anti-angiogenic treatments remains the development of resistance, mostly due to the upregulation and compensatory mechanisms of other g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 122 publications
1
29
0
Order By: Relevance
“…Since there is a strong connection between FGFs and angiogenesis [ 61 ], the reduction of FGFs levels is considered promising for inhibiting tumor development [ 62 , 63 ]. Among the FGFs, FGFb is one of the well-known pro-angiogenic factors [ 64 ], and in this study, we showed a significant reduction of FGFb levels after ApoE-Nut-PNPs ​+ ​US stimulation. Although the literature reports that electric stimulation enhances angiogenesis in HUVECs by stimulating FGF2 secretion [ 65 ], our findings show as the FGFb levels decreased upon ApoE-Nut-PNPs ​+ ​US administration.…”
Section: Discussionsupporting
confidence: 67%
“…Since there is a strong connection between FGFs and angiogenesis [ 61 ], the reduction of FGFs levels is considered promising for inhibiting tumor development [ 62 , 63 ]. Among the FGFs, FGFb is one of the well-known pro-angiogenic factors [ 64 ], and in this study, we showed a significant reduction of FGFb levels after ApoE-Nut-PNPs ​+ ​US stimulation. Although the literature reports that electric stimulation enhances angiogenesis in HUVECs by stimulating FGF2 secretion [ 65 ], our findings show as the FGFb levels decreased upon ApoE-Nut-PNPs ​+ ​US administration.…”
Section: Discussionsupporting
confidence: 67%
“…Despite the lack of direct reports on the pro-angiogenic effect of FGF in ocular tumors, it is reasonable to assume that its mere expression contributes to sustaining neo-vessel formation. Notably, anti-FGF approaches have been widely characterized as anti-angiogenic; furthermore, they can be employed to overcome resistance to conventional anti-VEGF therapies [ 91 , 92 ]. Interestingly, the anti-angiogenic effect exerted anti-FGFs/FGFRs should be considered from the perspective of an integrate approach, aimed at treating ocular tumors by acting on both the stromal and the parenchymal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, curcumin may decrease the activity of FGF-induced neovascularization ( 183 ). Previous studies have revealed the angiogenic synergy between bFGF and VEGF pathway ( 184 186 ). bFGF may also increase the expression of pro-angiogenic factors, including VEGF, to regulate the angiogenic processes ( 187 , 188 ).…”
Section: Curcuminmentioning
confidence: 99%